Diverse Activity Rhythms in Sharks (Elasmobranchii). Issue 5 (October 2020) - Kelly, Michael L.; Murray, Errol R. P.; Kerr, Caroline C.; Radford, Craig A.; Collin, Shaun P.; Lesku, John A.; Hemmi, Jan M.
Sharks are an interesting group of vertebrates, as many species swim continuously to "ram" oxygen-rich seawater over their gills (ram ventilators), whereas other species "pump" seawater over their gills by manipulating buccal cavity volume while remaining motionless (buccal pumpers). This difference in respiratory physiology raises the question: What are the implications of these differences in lifestyle for circadian rhythms? We investigated the diel activity patterns of 5 species of sharks, including 3 ram ventilating species: the school shark ( Galeorhinus galeus ), the spotted estuary smooth-hound ( Mustelus lenticulatus ), and the spiny dogfish ( Squalus acanthias ); and 2 buccal pumping species: the Port Jackson ( Heterodontus portusjacksoni ) and draughtsboard ( Cephaloscyllium isabellum ) sharks. We measured the amount, duration, and distance traveled while swimming over multiple days under a 12:12 light:dark light regime for all species and used modified light regimes for species with a clear diel rhythm in activity. We identified a surprising diversity of activity rhythms. The school shark and smooth-hound swam continuously; however, whereas the school shark swam at the same speed and covered the same distance during the day and night, the smooth-hound swam slower at night and traversed a shorter distance. A similar pattern was observed in the spiny dogfish, although this shark swam less overall. Both the Port Jackson and draughtsboard sharks showed a marked nocturnal preference for swimming. This pattern was muted and disrupted during constant light and constant dark regimes, although circadian organization of this pattern was maintained under certain conditions. The consequences of these patterns for other biological processes, such as sleep, remain unclear. Nonetheless, these 5 species demonstrate remarkable diversity within the activity rhythms of sharks.